2014
DOI: 10.5194/nhess-14-1417-2014
|View full text |Cite
|
Sign up to set email alerts
|

Flood design recipes vs. reality: can predictions for ungauged basins be trusted?

Abstract: Abstract. Despite the great scientific and technological advances in flood hydrology, everyday engineering practices still follow simplistic approaches that are easy to formally implement in ungauged areas. In general, these "recipes" have been developed many decades ago, based on field data from typically few experimental catchments. However, many of them have been neither updated nor validated across all hydroclimatic and geomorphological conditions. This has an obvious impact on the quality and reliability … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 43 publications
0
42
0
1
Order By: Relevance
“…Nevertheless, this is not true for all Mediterranean catchments. A recent study by Efstratiadis et al (2014), who analysed several flood events in small catchments in Greece and Cyprus, highlighted that the key component of flood runoff is interflow, not overland flow. The authors also demonstrated that the initial soil moisture conditions drastically influence the basin response (which is a common conclusion of all studies in the Mediterranean).…”
Section: Rainfall-runoff Event-based Studiesmentioning
confidence: 99%
“…Nevertheless, this is not true for all Mediterranean catchments. A recent study by Efstratiadis et al (2014), who analysed several flood events in small catchments in Greece and Cyprus, highlighted that the key component of flood runoff is interflow, not overland flow. The authors also demonstrated that the initial soil moisture conditions drastically influence the basin response (which is a common conclusion of all studies in the Mediterranean).…”
Section: Rainfall-runoff Event-based Studiesmentioning
confidence: 99%
“…This left the hydrological community with a wide range of methods that can improve the reliability of predictions in ungauged basins, but the lack of model validation methods in real case studies hinders a widespread use of these models. This is also expressed by Efstratiadis et al (2014), who discussed model realism in truly ungauged case studies. They concluded that flood design and modeling in ungauged basins is more than "blind application of recipes, " and one should carefully assess to what extent modeling results can be trusted.…”
Section: Pub Heritagementioning
confidence: 89%
“…Within these 10 years, the hydrological community developed a wide variety of new data acquisition techniques and approaches for hydrological modeling, to allow better estimations of model uncertainty and hydrological behavior in ungauged catchments. Although this resulted in a set of new tools and methods it remains difficult to put PUB into practice (Efstratiadis et al, 2014). We believe that this is strongly related to the fact that clear validation methods in PUB are still missing and are therefore omitted in many cases.…”
Section: Introductionmentioning
confidence: 99%
“…The above formula has been extracted and validated according to average CN-values obtained from the analysis of numerous flood events in a number of experimental river basins in Greece and Cyprus (Efstratiadis et al, 2014b). The minimum value of CN parameter is 28, while the maximum is 100.…”
Section: Novel Gis-based Framework For Cn Estimationmentioning
confidence: 99%